Teaching professional development evaluation: a territorial need. - Clara Esther Gómez Gonzalvo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Today is a fact the creation of new educational scenarios and the incorporation of professionals to the activity of the teaching. The heterogeneity of the formation of those professionals, the varied origin of the students, the inexperience of the directive of the system of health in the educational activity and the distance of the new scenarios of the centers of academic tradition, they are elements that determine the necessity to trace strategies of development educational professional to short, medium and long term. This work has the objective of basing theoretically, the election of the pattern for the identification and the evaluation of necessities of development educational professional, keeping in mind the particularities of our context.